Laman Minda Sihat: Kolaborasi Pendampingan Psikologis Siswa oleh Konselor Indonesia-Malaysia Melalui Terapi Hortikultura - Harahap, Ade Chita Putri; Harahap, Dinda Permatasari; Simarmata , Sari Wardani; Pratiwi, Awalya Siska; Nengsih, Nengsih; Johari, Alya Aqilah binti Ahmad (Universitas Nahdlatul Ulama Sumatera Utara, 2025)
The Laman Minda Sihat program is a form of collaboration between Indonesian and Malaysian counselors in providing psychological support to students thru a horticultural therapy approach. This activity will be held at SK Bandar Puteri Jaya, Sungai Petani, Kedah, Malaysia on October 8, 2024, with the aim of improving students' psychological well-being thru activities that align with their interests and talents. This counselling service emphasizes a humanistic and reflective approach, where students are directly involved in planting their chosen plants as a form of therapy. The mentoring process is carried out in several stages, starting from observation, question-and-answer sessions with the counselor, plant selection, to self-reflection after the activity. This planting activity aims to help students express themselves, overcome negative emotions, and cultivate responsibility and self-confidence. The results of the activity show that using the Laman Minda Sihat website as a counselling medium is able to have a positive effect on students' behavioral changes, particularly in increasing learning motivation and reducing problematic behavior. This cross-country collaboration also strengthens the application of cross-cultural counselling principles and enriches counselling guidance practices in primary education settings. The horticultural therapy approach has proven effective in improving students' emotional, social, and psychological well-being thru a harmonious relationship with nature and the application of positive reinforcement in the counselling process.